Evaluation of different varieties of mulberry (Morus alba) in the control of the methanogenesis in buffalo rumen liquid - Gonz?lez, Niurca; Galindo, Juana; Aldana, Ana Irma; Moreira, Onidia; Sarduy, Luc?a; Abdalla, L. A.; Duarte, M. Regina (Cuban Journal of Agricultural Science, 2010)
The methane production in rumen causes atmospheric harms and reduces animal productivity. The goal of this study was to evaluate the effect of four varieties of mulberry (Morus alba) on the total gas and methane production under in vitro conditions and select the most promising variety in the control of the river buffalo rumen methanogenesis. A complet random design with factorial fit (5 x 5) was used to evaluate five treatments: 1) 100 % of star grass (SG) (Cynodon nlemfuensis) (control), 2) SG + 30 % Cubana variety, 3) SG + 30 % Acorazonada variety, 4) SG + 30 % Tigreada variety, and 5 ) SG + 30 % Indonesia variety. The in vitro gas production technique was used, and the volumes of gas and methane produced were measured at 4, 8, 12, and 24 h of incubation. It was observed that the gas production was increased in time for all the treatments. At 24 h of incubation, the four varieties of mulberry (Morus alba) produced more gas than the control, and the Indonesia variety was the one that produced gas the most (102.36 mL gas/g of DM). The methane production was similar between the control and the treatment with 30 % of the Cuban variety (99.74 and 89.13 ?L/g of DM, respectively). As compared to the control, the varieties Acorazonada, Tigreada, and Indonesia produced more methane. Out of them, Indonesia was the one that produced the most. It was concluded that the 30 % inclusion of the varieties evaluated did not decrease the methane production in rumen. It is recommended to evaluate other levels of inclusion of the Cubana variety to attain higher reduction in the methane production. Key words: methane, gas production, rumen.